POSSIBILITIES OF SIMULATION MODELS VISUALIZATION IN TEACHING PROCESS - Grabusts, Peter (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Teaching experience shows that during educational process student perceive graphical information better than analytical relationships. Many educational courses operate with models that were previously available only in mathematics and physics disciplines. As a possible solution, there could be the use of package Matlab Simulink in realization of different algorithms both for engineering disciplines and economic studies. The paper presents examples of using simulation modelling in the educational research processes.